Torn between two nations: Aspects of loyalty in the case of Hungarian immigrants in the United States in 1917-1919 - Ambrus, László (Études sur la Région Méditerranéenne, 2020)
Immigration from the territory of Austria-Hungary in the United States had been at its peak in the decade before World War One. Approximately 1.5 million Hungarians were living in the US in the years preceding the Great War – some of whom were temporary immigrant labor, but the majority was seeking permanent stay or even citizenship. When the war broke out, thousands of Hungarians indicated their intention to travel home and enlist in the Hungarian army, other tens of thousands stayed in the US but attempted to help by sending money or supplies to the troops fighting in the frontlines. Soon, questions started to rise about where the loyalty of these ‘hyphenated’ immigrants’ lied. After the US entered the war in April, 1917, immigrants from Austria-Hungary were categorized as ‘enemy aliens’ under the Selective Service Act. However, roughly 3000 of them ended up serving in the American Military. Although Hungarian communities were not targeted with xenophobic attacks as much as their German counterparts, but they definitely faced atrocities for being ‘enemy aliens’. The paper will look into the way Hungarian immigrants experienced the war. It aims to explore how Hungarian communities were affected by war propaganda, conducted by both the American and the Austro-Hungarian governments. The paper will also attempt to reveal how Hungarian-Americans discussed news from the frontlines. It will seek answers to the following questions: How did they react to certain events? How did they see the role of Austria and Germany in the war? What did they think about the Hungarian, and the American involvement in the Great War? For whom were they “rooting”? The research is based on two main source groups: primary source records from American archives, and contemporary, predominantly Hungarian-American newspaper articles. Additionally, relevant works of secondary literature will be explored and utilized.